Fulfillment of Human Rights to a Good and Healthy Environment in the Perspective of Spatial Planning in Pematangsiantar - Banjarnahor, Daulat Nathanael; Togatorop, Firinta (CV RIFAINSTITUT, 2024)
Indonesia as a constitutional state, as well as a modern state, has a clear characteristic, namely that it clearly states the regulation of human rights in its constitution, the 1945 Constitution. Article 28H paragraph (1) of the 1945 Constitution states that